Collaborative clinical facilitation in selected nursing and midwifery colleges in Northern Ghana - Francis Kobekyaa; Joanne R. Naidoo (AOSIS, 2023)
Background: Collaborative clinical facilitation converges key players to guide students individually and within groups towards achieving clinical nursing competence. However, experiences of collaborative clinical facilitation among nurse educators, clinical preceptors and nursing and midwifery students are often fragmented and have been largely unexplored in Ghana. Aim: To describe the experiences of collaborative clinical facilitation among nurse educators, clinical preceptors and final year nursing and midwifery students in Northern Ghana. Setting: The study was conducted at two nursing and midwifery colleges and an academic hospital in Northern Ghana. Methods: A qualitative, descriptive, exploratory design was utilized. Forty-six participants comprising 16 nurse educators, 10 clinical preceptors, 10 nursing students and 10 midwifery students were purposively sampled. Focus groups and in-depth interviews were used to gather data and analysed thematically. Results: Three themes revealed facilitative experiences of collaborative clinical facilitation: team-based clinical mentorship and supervision, personalised preceptorship, and clinical conferences. Two themes emerged inhibitory to collaborative clinical facilitation: staff shortages and lack of timely communication. Conclusion: This study found that team mentorship, preceptorship and conferences fostered collaborative clinical partnerships for students' clinical learning. However, failure to engage in timeous communication in the midst of staff shortages hampered its smooth practice. Orientation workshops need to be organised for key players to share relevant updates and explore ways to navigate the challenges often experienced within the clinical training environment. Contribution: This paper provides insight into the collaborative nature of clinical facilitation; and highlights the need for coordinated clinical placements to enhance students' clinical learning.